Rancang Bangun Sistem Informasi Persediaan Barang Menggunakan Framework Laravel dengan Metode Waterfall: Studi Kasus Toko Amora Computer - Andrean Bagus Saputra; Jemiro Kasih (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
Amora Computer Store is a medium-sized retail shop that sells all types of computers, laptops, and other computer accessories. Amora Computer Store still uses conventional methods for recording incoming goods, sales, company debts, and employee salaries. This research aims to manage inventory and sales in a computerized manner by building an Inventory Information System. The type of research used is Qualitative. Qualitative research employs numerical data such as texts, interviews, and observations to understand phenomena in depth. The research stages utilize the Waterfall method, which is a Software Development Life Cycle (SDLC) method used for software development. The advantage of this method is that the resulting system development will be better because the system development is carried out in stages. This research uses the Laravel Framework, which is easy to implement with the MVC (Model, View, Controller) concept, creating a tidy data structure by separating the presentation from data processing. Based on the results of testing the system's functionality using the User Acceptance Testing (UAT) method by completing 70 testing scenario questions, a result of 97.17% was obtained, indicating that 68 scenarios functioned as expected, while 2.86% or 2 scenarios did not function as expected. In conclusion, the system's functionality operates as anticipated.